Identification of Escherichia coli Sub Type Enterotoxigenic (ETEC) from Food Samples Using Pcr (Polymerase Chain Reaction) Technique - Deby Anggryani; Edy Kurniawan; Dhika Juliana Sukmana; Jumari Ustiawaty (Jurnal Biologi Tropis, 2023)
Escherichia coli is a normal flora of the digestive tract of humans and animals and is important in the digestion of food. This bacteria lives in feces, can cause health problems, such as diarrhea and vomiting. This research was conducted for consideration in the prevention of diarrhea, processing, marketing of food. This study aims to determine the presence of enterotoxigenic Escherichia coli sub-type (ETEC) from food samples. This research is an explorative descriptive study, as many as 5 samples from food, food samples taken are food consumed every day and some include traditional food in Mataram City. The samples were cultured on BHI-Broth media, followed by inoculation on Eosin Methylene Blue (EMB) medium and continued with the Gram stain test. Colonies that are metallic green in colour and show the characteristics of Escherichia coli bacteria on Gram staining are then carried out for purification of the bacteria on Nutrient Agar (NA) medium, if the classification of bacteria shows the characteristics of Escherichia coli bacteria on Gram staining then proceed with the Indole/sugar-test. The results showed that of the 5 food samples isolated, only 1 sample showed positive E.coli bacteria. Then proceed to the PCR (Polymerase Chain Reaction) stage using the qualitative PCR method to determine the presence of Enterotoxigenic Escherichia coli sub-type (ETEC) bacteria in food samples. , with a target gene of 237 bp.